Efektivitas video animasi edukasi gizi berbasis instagram reels terhadap emotional eating dan konsumsi makanan cepat saji pada remaja obesitas sentral - Arifa Aulia Fatihaturrahma; Tri Rejeki Andayani; Anik Lestari (Jurnal SAGO Gizi dan Kesehatan, 2026)
Background: Central obesity is a growing health problem among adolescents due to unhealthy eating patterns and fast food consumption habits. One of the triggering factors is emotional eating, which is overeating in response to emotions rather than physiological hunger. Nutrition education is an important strategy for obesity prevention; however, it needs to be tailored to the characteristics of adolescents, who are attracted to visual and digital media content. The use of social media, such as Instagram, is considered effective for conveying nutrition messages in an engaging and easily accessible way.Objective: This study aimed to analyze the effectiveness of animated nutrition education videos on Instagram Reels on emotional eating behavior and fast food consumption in adolescents with central obesity in Palu City.Methods: This study used a quasi-experimental design with a pretest-posttest control group. The study was conducted from July to September 2025 at SMA Model Terpadu Madani and SMA Al-Azhar Palu, and 34 students with central obesity were selected by purposive sampling.  Data were collected using the Emotional Eating Questionnaire (EEQ) with a Cronbach's alpha reliability value (α = 0.829) and the Food Frequency Questionnaire (FFQ) with a reliability value (α = 0.802) to assess fast food consumption. Data analysis was performed using the Mann–Whitney U test for comparisons between groups and the Wilcoxon signed-rank test for comparisons within the groups.Results: The results of the animated video research showed a decrease in emotional eating behavior scores and fast food consumption in the intervention group (p<0,05).Conclusion: An Instagram Reels-based nutrition education animation video has the potential to reduce emotional eating levels and fast food frequency in centrally obese adolescents.